2020
DOI: 10.1111/coa.13497
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of preoperative platelet‐to‐lymphocyte ratio and platelet‐related indices in advanced hypopharyngeal squamous cell carcinoma

Abstract: Objectives To investigate the prognostic values of preoperative platelet‐to‐lymphocyte ratio (PLR) and platelet‐related indices in advanced hypopharyngeal squamous cell carcinoma (HPSCC). Methods The data of 247 eligible advanced HPSCC patients were reviewed retrospectively. Pretreatment haematological parameters were categorised into two groups based on the result of X‐tile, and several variates were assessed using chi‐square test, Kaplan‐Meier method, Cox univariate and multivariate analysis. Results The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The PLR was demonstrated to be an independent predictor of diabetes with chronic complications [38][39][40] and tumors (such as non-small-cell lung cancer and hypopharyngeal squamous cell carcinoma) [41,42]. Recent studies proved that PLR is related to the prognosis of stroke thrombolysis [43] or endovascular treatment [44].…”
Section: Plos Onementioning
confidence: 99%
“…The PLR was demonstrated to be an independent predictor of diabetes with chronic complications [38][39][40] and tumors (such as non-small-cell lung cancer and hypopharyngeal squamous cell carcinoma) [41,42]. Recent studies proved that PLR is related to the prognosis of stroke thrombolysis [43] or endovascular treatment [44].…”
Section: Plos Onementioning
confidence: 99%
“…Our previous study showed that preoperative lymphocytes, NLR, PLR, and LMR are significantly associated with laryngeal squamous cell carcinoma (LSCC) progression, DFS, and cancer-specific survival and that these hematological parameters could be considered as independent prognostic values in patients with LSCC [5]. Another previous work showed that LMR is an independent prognostic factor in patients with HPSCC [38]. One of our recent studies proved that low PLR or mean platelet volume may be an independent predictor of better prognosis regarding both OS and DFS in patients with advanced HPSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the formation and development of tumors often require blood as the carrier, hematology markers and molecular biomarkers have gradually become the focus of most clinicians. Some studies have shown that parameters such as the preoperative NLR, PLR, and LMR are closely related to prognosis in patients with various cancers, such as head and neck squamous cell cancer [26,28,35,[37][38][39]. In addition, compared with many other prognostic factors, inflammation-based prognostic parameters offer the advantages of simplicity, wide usage, and low cost in terms of preoperative evaluations with blood tests.…”
Section: Discussionmentioning
confidence: 99%
“…We consider 109.75, a value lower than 111.26, is inappropriate to be used as a practical cutoff, since a higher PLR is related to higher risks. PLR cutoff value for the hypopharynx was higher than their laryngeal counterparts, but due to limited hypopharyngeal cases, a critical appraisal was not separately made [19,20].…”
Section: Selection Of Plr Cutoff Value Could Influence On Stratifying Patientsmentioning
confidence: 99%